2001
DOI: 10.1002/path.929
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of IL-10 and IFN-? mRNA levels in normal cervix and human papillomavirus type 16 associated cervical precancer

Abstract: Human papillomavirus type 16 is a major factor in cervical carcinogenesis. Inappropriate cytokine synthesis may direct the local immune response away from a type-1 (cellular) pattern and may subsequently contribute to the development and progression of precancer. Quantitative reverse transcription-polymerase chain reaction (RT-PCR) using a competitive mimic was carried out to determine type-1 (interferon gamma (IFN-gamma)) and type-2 (interleukin-10 (IL-10)) cytokine mRNA levels in whole cervical specimens (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 47 publications
4
46
1
3
Order By: Relevance
“…10 In addition, IFN-k mRNA was absent in raft cultures containing collagen and fibroblasts only (stroma equivalent), that is without keratinocytes, MCs or DCs in this study, which further supports the specific role of lymphoid populations in the stromal IFN-k induction. In line with IL-10 mRNA levels in this study, IL-10 has previously been found to be elevated in diseased cervical tissue 41 and in peripheral blood mononuclear cells of patients with extensive cervical disease. 42 However, the cause of the IL-10 elevation had not been addressed in these studies.…”
Section: Discussionsupporting
confidence: 88%
“…10 In addition, IFN-k mRNA was absent in raft cultures containing collagen and fibroblasts only (stroma equivalent), that is without keratinocytes, MCs or DCs in this study, which further supports the specific role of lymphoid populations in the stromal IFN-k induction. In line with IL-10 mRNA levels in this study, IL-10 has previously been found to be elevated in diseased cervical tissue 41 and in peripheral blood mononuclear cells of patients with extensive cervical disease. 42 However, the cause of the IL-10 elevation had not been addressed in these studies.…”
Section: Discussionsupporting
confidence: 88%
“…In women with HPV16-positive CIN, El-Sherif et al observed decreased levels of IFNÁ and TGFß mRNA and increases of IL-10 compared to healthy HPV-negative controls (36,37). Others recently found that elevations in IFNÁ and IL-10 were associated with decreased odds of having CIN 2 or 3 (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that only IFN-γ positive results were significantly associated with clearance of HR-HPV after 12 months of follow-up (Song et al, 2008). The microdissections of 11 normal cervixes and 25 HPV-16 positive CIN cervixes were studied and the researchers suggested that reduced epithelial and sub-epithelial IFN-γ, as well as increased sub-epithelial IL-10 synthesis, may play a role in the development and progression of HPV16 associated cervical pre-cancer (El-Sherif et al, 2001). Alterations of the local cervical immune environment in cervical cancer were demonstrated in a study that analyzed the presence of various cytokines in CVLs of 22 healthy volunteers, 63 CIN patients and 33 cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%